Nested multi-scale transform fusion model: The response evaluation of chemoradiotherapy for patients with lung tumors. (April 2023) - Zhou, Tao; Liu, Shan; Lu, Huiling; Bai, Jing; Zhi, Lijia; Shi, Qiu
Highlights: Constructing a nested multi-scale transform temporo-spatial fusion model. Realizing PET/CT fusion of patient's different chemoradiotherapy periods. The attribute sets for response evaluation of chemoradiotherapy is developed. Constructing a response evaluation of chemoradiotherapy for lung tumor patients. Abstract: Background and Objective: The response evaluation of chemoradiotherapy is an important method of precision treatment for patients with malignant lung tumors. In view of the existing evaluation criteria for chemoradiotherapy, it is difficult to synthesize the geometric and shape characteristics of lung tumors. In the present, the response evaluation of chemoradiotherapy is limited. Therefore, this paper constructs a response evaluation system of chemoradiotherapy based on PET/CT images. Methods: There are two parts in the system: a nested multi-scale fusion model and an attribute sets for the Response evaluation of chemoradiotherapy (AS-REC). In the first part, a new nested multi-scale transform method, i.e., latent low-rank representation (LATLRR) and non-subsampled contourlet transform (NSCT), is proposed. Then, the average gradient self-adaptive weighting is used for the low-frequency fusion rule, and the regional energy fusion rule is used for the high-frequency fusion rule. Further, the low-rank part fusion image is obtained by the inverse NSCT, and the fusion image is generated by adding the low-rank part fusion image and the significant part fusion image. In the second part, AS-REC is constructed to evaluate the growth direction of the tumor, the degree of tumor metabolic activity, and the tumor growth state. Results: the numerical results clearly show that the performance of our proposed method outperforms in comparison with several existing methods, among them, the value of Qabf increased by up to 69%. Conclusions: Through the experiment of three reexamination patients, the effectiveness of the evaluation system of radiotherapy and chemotherapy are proved. Graphical abstract: Image, graphical abstract